2016
DOI: 10.1038/leu.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitor-adapted myeloma cells are largely independent from proteasome activity and show complex proteomic changes, in particular in redox and energy metabolism

Abstract: Adaptive resistance of myeloma to proteasome inhibition represents a clinical challenge, whose biology is poorly understood. Proteasome mutations were implicated as underlying mechanism, while an alternative hypothesis based on low activation status of the unfolded protein response was recently suggested (IRE1/XBP1-low model). We generated bortezomib- and carfilzomib-adapted, highly resistant multiple myeloma cell clones (AMO-BTZ, AMO-CFZ), which we analyzed in a combined quantitative and functional proteomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
153
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(170 citation statements)
references
References 29 publications
16
153
0
1
Order By: Relevance
“…However, in individual cases, rare gene mutations may impact treatment decisions. For example, CRBN , IKZF1 or IKZF3 mutations (totaling a combined 1.6% of patients in our cohort) would predict resistance to IMiDs 26 , whereas XBP1 deletions could predict bortezomib-resistance 38 , suggesting future clinical-grade targeted platforms must include rare driver events that have predictive value for treatment.…”
Section: Discussionmentioning
confidence: 93%
“…However, in individual cases, rare gene mutations may impact treatment decisions. For example, CRBN , IKZF1 or IKZF3 mutations (totaling a combined 1.6% of patients in our cohort) would predict resistance to IMiDs 26 , whereas XBP1 deletions could predict bortezomib-resistance 38 , suggesting future clinical-grade targeted platforms must include rare driver events that have predictive value for treatment.…”
Section: Discussionmentioning
confidence: 93%
“…62 A similar pattern of selectivity is observed for carfilzomib binding to the immunoproteasome. 63 More pertinently, lower levels of off-target protease inhibition are observed with carfilzomib than with bortezomib, including activity at the HtrA2/Omi protease; this may explain the difference in incidence of peripheral neuropathy associated with the 2 proteasome inhibitors. 58…”
Section: Arfil Zomibmentioning
confidence: 99%
“…Mutations in the PSMB5 gene, which codes for the proteasome β5-subunit protein, by diminishing proteasome inhibitor binding, may lead to the development of resistance 93 ; however, this has not been corroborated. 63 It is now believed that several pathways are involved in the development of proteasome inhibitor resistance. An in vitro study showed that the adaptation of MM cells exposed to bortezomib Krüppel-like transcription factor 4 (which leads to prosurvival cell destruction).…”
Section: Re S Is Tan Ce To Prote a Some Inhib Itor Smentioning
confidence: 99%
See 2 more Smart Citations